2015
DOI: 10.4103/1450-1147.150531
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Functioning of the Orchidopexied Congenital Undescended Testis as Assessed by Positron Emission Tomography/Computed Tomography

Abstract: Fertility after orchidopexied undescended testes (UDT) is impaired. Although fertility parameters are known to be more favorable in unilateral cases than in bilateral cases, the exact contribution of the unilateral orchidopexied UDT to fertility is unknown. We used testicular 18F-fluoro-2-deoxyglucose (18F-FDG)-uptake assessed by positron emission tomography/computed tomography (PET/CT) to investigate the function of the orchidopexied unilateral congenital UDT, compared to its normally descended counterpart. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Lastly, Meij-de Vries et al 32 reported that post-orchidopexy testes showed a statistically lower tracer uptake than the contralateral healthy testis. As it is known that testes post-orchidopexy show very low metabolic activity, the study findings suggested that the surgical procedure allows for some return of function into the affected testis.…”
Section: Results -Pet/ct For Functional Assessment Of Testesmentioning
confidence: 98%
See 2 more Smart Citations
“…Lastly, Meij-de Vries et al 32 reported that post-orchidopexy testes showed a statistically lower tracer uptake than the contralateral healthy testis. As it is known that testes post-orchidopexy show very low metabolic activity, the study findings suggested that the surgical procedure allows for some return of function into the affected testis.…”
Section: Results -Pet/ct For Functional Assessment Of Testesmentioning
confidence: 98%
“…Lastly, Meij‐de Vries et al 32 . reported that post‐orchidopexy testes showed a statistically lower tracer uptake than the contralateral healthy testis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation